PENGARUH Pengaruh Kebijakan Dividen terhadap Harga Saham Perusahaan sektor industrial goods di BEI - Anugrah, Safani; Saputra, Rizqy Imam; Surachman, Ade Elza (AkMen JURNAL ILMIAH, 2025)
This study aims to analyze the effect of dividend policy on stock prices in manufacturing companies in the industrial goods sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Using a quantitative approach and secondary data from 12 selected companies through purposive sampling, dividend policy is measured by the Dividend Payout Ratio (DPR), while stock prices are seen from the year-end closing. The results of simple linear regression analysis and T-test so that it can be concluded that dividend policy has a positive and significant effect on stock prices indicating that with T count> T table or 7.505> 2.001 with a significance level of 0.000 <0.05. This finding supports the signal theory that dividends reflect the company's prospects, and provides strategic implications for management in designing dividend policies that are attractive to investors.